Cytotoxic Activity of Indonesian Pogonatum neesii Dozy from Cibodas Botanical Garden: In Silico Molecular Docking and In Vitro Evaluation - Rizky Nurdiansyah; Agus Budiawan Naro Putra; Ainun Nadhifah; Erika Chriscensia; Ulung Khoe Gondo Kusumo; Stephanie Angela Yosiano; Anastasia Beatrix Musung; Sintikhe A Wenas; Steve Makalew; Patricia Lovina; Intani Quarta Lailaty; Fransisca Aurelia Rahmad; et al. (Tabriz University of Medical Sciences, 2023)
Background: The exploration of bryophytes biodiversity in Indonesia due to its abundance and the bioactivity of its phytochemical content, such as alkaloids and polyphenols, has received increased interest. Despite some species proven to possess pharmacological properties, the antiproliferative study of Indonesian native moss, such as the Pogonatum genus, is limited. Hence, this study aims to evaluate the anticancer effects of Pogonatum neesii Dozy antiproliferative activity on colon and cervical cancer through in silico and in vitro methods. Methods: Molecular docking analysis using Autodock VINA in PyRx softwre was conducted between natural compounds found on P. neesii and several target proteins, DNA (cytosine-5)- methyltransferase 1 (DMT-1) (Protein Data Bank (PDB) id: 4WXX) in colon cancer and B-cell lymphoma 2 (Bcl-2) (PDB id: 4LXD) in cervical cancer. Afterwards, total phenolic and alkaloid contents were measured. Subsequently, P. neesii was tested on HaCaT (keratinocytes), HEK293 (human embryonic kidney), HT-29 (colorectal cancer models) and HeLa (cervical cancer model) to observe its cytotoxicity. Results: Out of eight compounds, chlorogenate was found to exert the best binding energy with target proteins, although it had lower binding affinity than the protein's natural ligand. However, the biological, drug-likeness, and toxicity analysis suggested the drug potency of the compound, thus we did the in vitro analysis. P. neesii showed significant cytotoxic effects on HT-29 and HeLa cells, while it did not exert any cytotoxic effects on HaCaT and HEK-293 cells, at the same concentrations. Conclusion: P. neesii has been shown to have the potential as an anticancer agent through in silico and in vitro analysis, where the extract showed selective cytotoxicity towards cancer cell lines and cytocompatibility towards normal cell lines. Chlorogenate was pinpointed as the compound with the most activity and interaction with the target proteins in both cancers.